2012
DOI: 10.1080/09638199.2010.497933
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous evolution of economic growth, financial development, and trade openness

Abstract: This article empirically investigates the interactions among economic growth, financial development, and trade openness through simultaneous equation systems. The identification and estimation of the systems rely on the methodology of identification through heteroskedasticity. The empirical results show that each of the three variables interacts in important ways. When controlling for the reverse causation, trade promotes economic growth in high-income, low-inflation, and nonagricultural countries but has a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 78 publications
2
45
2
Order By: Relevance
“…Trade openness is conducive to economic growth in low-inflation countries but has insignificant impact on growth in high-inflation countries. Kim, Lin, and Suen (2012) provide evidence that trade promotes economic growth in high-income, low-inflation, and non-agricultural countries but has a negative impact in countries with the opposite attributes. For a panel of 46 countries, Huang and Chang (2014) find that the growth effect of trade depends on the extent of stock market development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trade openness is conducive to economic growth in low-inflation countries but has insignificant impact on growth in high-inflation countries. Kim, Lin, and Suen (2012) provide evidence that trade promotes economic growth in high-income, low-inflation, and non-agricultural countries but has a negative impact in countries with the opposite attributes. For a panel of 46 countries, Huang and Chang (2014) find that the growth effect of trade depends on the extent of stock market development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even for the most part, rigorous financial reforms in Africa and attempts at international market integration have not yielded the desired economic performance. Meanwhile, a growing number of studies have confirmed the trade-enhancing effect of finance (see Beck, 2002;Kim, Lin, & Suen, 2012). UNCTAD (2005UNCTAD ( , 2007, however, suggests that limited level of financial systems exacerbates the transaction costs as a trade barrier if none of the trading partners are able to offer the trade financing.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rajan and Zingales (2003), an increase in both cross-country trades and capital flows leads to an increase in the degree of financial development. Saleryd and Vlachos (2002), Beck (2002) and Kim et al (2012) find a reverse causal effect between trade openness and financial development (i.e. the increase in trade openness occurs following an increase in financial development).…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Thirdly, companies could increase their profitability not only indirectly through the change in their asset values, but also directly through the increase in overall productivity in regions with high UEO ( (Demsets 1973, Peltzman 1977, Eilon 1985, Jovanovic 1982, Stierwald 2010. 2 Finally, an increase in the UEO of a city can also lead to a rise in property prices by fostering an increase of foreign (and domestic) real estate investments in more open regions, due to an easier flow of capital- Saleryd and Vlachos (2002), Beck (2002), Basu and Morey (2005), Law (2008), Baltagi et al (2009), Lim and Kim (2011) and Kim et al (2012). Overall, the above mechanisms demonstrate how UEO can decrease the uncertainty about the company's future earnings, leading to a more accurate firm valuation.…”
Section: Introductionmentioning
confidence: 99%